INTERNET LITERACY LEVEL OF THE STUDENTS OF ENGLISH DEPARTMENT ISLAMIC UNIVERSITY OF LAMONGAN (UNISLA) - Nurman, Mohammad (TELL - US JOURNAL, 2019)
This present study aims at investigating the internet literacy level of the eighth semester students of English Department, UNISLA, in the academic year of 2018/2019” which focused on search engine, social media, e-mail and downloading. This study employed the descriptive survey approach. The research population comprised all third semester students of English Department UNISLA in the academic year 2018/2019. The number of populations was 110 students.  But 97 students became as the subjects of the study assigned randomly. The data were analyzed through descriptive statistic. The result of the study shows that in terms of the skill of using general internet application, 48% of the students got fair. Related to “Do you” and “Can you” questions, most of the students or 87% of them responded ‘yes”. Then, in relation to their general internet knowledge, their level belonged to middle class or fair level, that is, 59 or 60%.